Contextualizing the Hadith on Tying Hair in a Ponytail during Prayer: A Ma'ani al-Hadis Study - Dwi Junita, Rina; Muhajirin, Muhajirin; Zulfikar, Eko (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2024)
This article examines the hadith prohibiting someone from wearing a ponytail when performing prayer. There are so many hairstyles nowadays and demands, this is difficult for some people, both men and women, to avoid. Is it contrary to the hadith of the Prophet or not! This is interesting to research further. How to understand the hadith in the current context is a solution to find answers put forward using the ma'ani al-hadith method, so that the hadith is contextualized according to current developments. By using qualitative methods, this article concludes that the understanding of the hadith above is that there are provisions for the period in which it occurred. The hadith prohibition of wearing hair in a ponytail during prayer can actually change into a separate context so that it can be changed to allow wearing hair in a ponytail during prayer. Contextualization in this context refers to efforts to understand and interpret a religious teaching or commandment, in this case the hadith, by considering different cultural, social and time contexts. In this case, contextualizing the hadith "prohibition of wearing hair in a ponytail during prayer" involves understanding that the rule may be adapted to current realities that are different from the time in which the hadith was conveyed. This emphasizes that the understanding and application of Islamic law is not static, but can adapt to changing times and different social conditions.